Stabilization of hyaluronan-based materials by peptide conjugation and its use as a cell-seeded scaffold in tissue engineering - Karel, Sergej; Sogorkova, Jana; Hermannova, Martina; Nesporova, Kristina; Marholdova, Lucie; Chmelickova, Kristyna; Bednarova, Lucie; Flegel, Martin; Drasar, Pavel; Velebny, Vladimir (Carbohydrate polymers, 2018)
New materials based on molecules naturally occurred in body are assumed to be fully biocompatible and biodegradable. In our study, we used hyaluronic acid (HA) modified with peptides, which meet all this criterion and could be advantageously used in tissue engineering. Peptides with RGD, IKVAV or SIKVAV adhesive motif were attached to HA-based fiber or non-woven textile through ester bond in the term of solid phase peptide synthesis. A linker between HA and peptide containing three glycine or two 6-aminohexanoyl units was applied to make peptides more available for cell surface receptors. Dermal fibroblasts adhered readily on this material, preferentially to RGD peptide with 6-aminohexanoyl linker. Contrary, the absence of adhesive peptide did not allow the cell attachment but maintained the material stability.
Keywords: Tissue Engineering; Non-woven textiles; Humans; tkáňové inženýrství; RGD; SPPS; Tissue Scaffolds; Dermis; Cell Adhesion; lidé; Hyaluronan; peptidy; Peptides; tkáňové podpůrné struktury; kyselina hyaluronová; škára; fibroblasty; buněčná adheze; Fibers; Hyaluronic Acid; Cell adhesion; Fibroblasts